Potential Transmission of Zoonotic Tuberculosis Disease from Livestock to Humans - Hasna Aldisa Madani; Adi Imam Cahyadi (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Zoonotic Tuberculosis (Ztb) is caused by member of group bacteria called Mycobacterium tuberculosis complex which can attack animals as reservoirs and is zoonotic so that it can be transmitted and infected humans. This paper aims to review about zoonotic tuberculosis which includes: causative agents, modes of transmission, risk factors and prevention of Ztb transmission from livestock to humans. Based on reviewing 47 literatures, it shows that zoonotic tuberculosis in livestock can be caused by Mycobacterium bovis, Mycobacterium caprae and Mycobacterium orygis. The disease is transmitted by inhalation and oral routes. The most common risk factors are types of livestock rearing, age of livestock and population or herds size. There are several measures to prevent Ztb transmitted from livestock to humans, such as improving the good maintenance management, implementation of routine surveillance program, increasing vaccination coverage and other preventive measures by taking into account all risk factors that can increase the incidence and transmission of Ztb.